Algorithm Effectiveness In Digital Content - Joval Ifghaniyafi Farras; Raden Rifqi Dwisanto (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to map the effectiveness of algorithms in digital content strategy across different industries and platforms through a systematic literature review of 50 selected articles published between 2016-2025. The focus of the review includes algorithmic personalisation, consumer engagement, ethical considerations, and recent technology trends. The results of the thematic analysis show that AI-based personalisation-through recommendation engines, predictive analytics, and generative AI-consistently improves content relevance, engagement, retention, conversion, and brand loyalty in sectors such as e-commerce, social media, and luxury branding. However, issues of privacy, algorithmic transparency, bias and the risk of content homogeneity remain significant challenges affecting user trust. Variations in effectiveness across industries and platforms indicate the need to customise strategies based on cultural context, demographic and technical characteristics of the platform. New trends such as influencer integration, real-time adaptive marketing and generative AI-based content show great potential, but require ethical governance and rigorous empirical testing. This study confirms the importance of balancing the benefits of algorithmic personalisation with privacy protection, content diversity and transparency to ensure the sustainability of digital marketing strategies in a dynamic ecosystem